Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1001/archpedi.156.8.794
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' and Health Care Providers' Perspectives on Screening for Intimate Partner Violence in a Pediatric Emergency Department

Abstract: Intimate partner violence screening protocols in the pediatric emergency department should take into consideration the beliefs and attitudes of both those doing the screening and those being screened. Those developing screening protocols for a pediatric emergency department should consider the following: (1) that those assigned to screen must demonstrate empathy, warmth, and a helping attitude; (2) the importance of addressing the child's medical needs first, and a screening process that is minimally disruptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 13 publications
1
84
0
6
Order By: Relevance
“…Nesse contexto, muitos autores têm recomendado que médicos e profissionais da saúde possam investigar em sua rotina clínica a questão da violên-cia doméstica (Thompson e Krugman, 2001). No entanto, as barreiras em termos desse tipo de comunicação são significativas (Dowd et al, 2002).…”
Section: Resultados Perfil Familiarunclassified
“…Nesse contexto, muitos autores têm recomendado que médicos e profissionais da saúde possam investigar em sua rotina clínica a questão da violên-cia doméstica (Thompson e Krugman, 2001). No entanto, as barreiras em termos desse tipo de comunicação são significativas (Dowd et al, 2002).…”
Section: Resultados Perfil Familiarunclassified
“…The cited reasons are similar to those for practitioners treating adults: feelings of inadequate education and too little time, and concern about offending patients [34,35]. Of note, focus groups fail to bear out the latter concern, as parents seem to acknowledge that these problems exist and have medical implications [36]. Alternatives to face-to-face screening have been found to be well-accepted and effective [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been identified however that in addition to the implementation of a particular process there also needs to be a clear and supportive infrastructure. Trautman et al (2007) have cited logistical problems, the absence of a social worker support for example, as a limitation to effective screening, while Dowd et al (2002) state that domestic abuse screening initiatives in ED 'need to take into account the attitudes and beliefs of those doing the screening' (Dowd et al 2002, p795).…”
Section: Introductionmentioning
confidence: 99%
“…Yam (2000) reported that women who attended an ED as a result of domestic abuse felt that staff had a 'rushed and hurried approach' (p469) towards them which further reinforced their reluctance to disclose the circumstances surrounding their admission. While Dowd et al (2002) highlighted that ED staff questioned the appropriateness of using ED resources to screen for domestic abuse. Within this context it has also been suggested that the organisational culture of the ED, where 'work flow', 'rapid interventions' and an emphasis on the technological aspects of care (Andersson et al, 2012) may mediate against disclosure of abuse (Yonaka, 2007).…”
Section: Introductionmentioning
confidence: 99%